Clinical Supervision Feedback to Enhance Teachers' Learning Agility - Puspita Dwi Permatasari; Rasiman Rasiman; Endang Wuryandini (Green Publisher Indonesia, 2024)
Education in the 21st century requires teachers with high learning agility to deliver quality learning experiences. One way to improve learning quality is through clinical supervision. This study focuses on the final stage of clinical supervision, the feedback session, as an effort to enhance teachers' learning agility. The research uses a descriptive qualitative method. Data is collected through interviews and documentation from the school principal, teachers, and students. The validity of the data is ensured through triangulation of methods and sources. The feedback session analyzes efforts to improve the dimensions of learning agility, namely social agility, mental agility, change agility, and results agility, through the clinical supervision feedback stage. In this final stage, teachers and the principal reflect on the teacher's strengths and areas for improvement together, discussing the necessary skill enhancement steps. The research shows that during the feedback session process, in addition to the four dimensions of learning agility, the dimensions of teacher flexibility and speed were also developed.